2019
DOI: 10.29333/ejecs/283
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic Stress Disorder Related to Trait Emotional Intelligence of Slovaks in Comparison to Turkish Immigrants in Slovakia

Abstract: Objective: The study aim was to investigate the differences and prediction of post-traumatic stress disorder (further PTSD) by trait emotional intelligence (further EI) and its four factors (well-being, self-control, sociability, and emotionality) of two specific groups. Method: Research groups were immigrants coming to Slovakia from Turkey (N=104, Mage=35.4 years, /SD=10.2/) and national majority of the Slovaks living in Slovakia (N=264, Mage=33.2 years /SD=11.9/). PTSD was assessed by PCL-5 (PTSD Checklist f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Author obtained the same results, who found that immigrants with severe PTSD symptoms lacked the ability to understand and use emotions [31] . The results of the study are also consistent with [32] , where higher levels of emotional intelligence were significantly associated with lower levels of PTSD, while low emotional intelligence was found in individuals with high PTSD who used destructive strategies of avoidance and distancing.…”
Section: Resultssupporting
confidence: 87%
“…Author obtained the same results, who found that immigrants with severe PTSD symptoms lacked the ability to understand and use emotions [31] . The results of the study are also consistent with [32] , where higher levels of emotional intelligence were significantly associated with lower levels of PTSD, while low emotional intelligence was found in individuals with high PTSD who used destructive strategies of avoidance and distancing.…”
Section: Resultssupporting
confidence: 87%
“…Olalowo (2020) argued that children's general opinions of themselves, particularly overage children's perceptions of self, will play a predictor in stimulating them to interact better with their classmates and teachers, consequently improving their socio-emotional abilities. These interactions eventually have a signi cant role in developing their cognition, which measures their mental health (Kaliska, 2019;Amosun, 2012). The ability to handle complex social situations, interact positively with peers, and develop friendships is vital to age-appropriate socio-emotional development (Buysse et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Robinson (2009) argued that immigrants who perceive discrimination prefer a separation strategy rather than that of integration or assimilation. Various research studies also revealed a relationship between identity and acculturation orientations (Badea, Jetten, Iyer, & Er-rafiy, 2011;Kaliska & Akbey, 2019;Nesdale, 2002;Nesdale & Mak, 2000;Safdar, Calvez, & Lewis, 2012). While some studies treat national or ethnic identity as an outcome of acculturation attitudes (e.g., Nesdale, 2002;Nesdale & Mak, 2000), others show that national or ethnic identification can predict acculturation (Badea et al, 2011;Safdar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%